1978
DOI: 10.1159/000241086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Administration of Hydrocortisone, Actinomycin D and Puromycin on Carbamoylphosphate Synthetase-I and Ornithine Carbamoyltransferase Activities in Fetal Rat Liver

Abstract: The administration of hydrocortisone (0.1 mg) to intact fetuses in utero on day 16.5, 17.5 and 18.5 caused a marked increase in the activity of carbamoylphosphate synthetase-I 48 h later. This increase can be abolished 48 h later by simultaneous administration of actinomycin D (2 μg). No change in the activity of ornithine carbamoyltransferase was found with administration of hydrocortisone in utero during the same period. The normal increase of the activity of carbamoylphosphate synthetase-I during the late f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Consequently, the hormone might act by two different ways on enzyme activity: directly by increasing enzyme synthesis and probably indirectly by facilitating the inhibi tory effect of insulin on enzyme activity. This hypothesis is consistent with our previous findings [6]: glucocorticoid supply partially overcomes the paradoxical effect of actinomycin D on enzyme activity. Since the stim ulatory effect of the antibiotic on OTC activ ity is associated with a decrease in insulincmia, glucocorticostcroids and the high level in fetal insulinentia [3,18] might act as inhib itory factors on enzyme development, sug gesting a permissive effect of glucocorticosteroids on insulin action in vivo.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Consequently, the hormone might act by two different ways on enzyme activity: directly by increasing enzyme synthesis and probably indirectly by facilitating the inhibi tory effect of insulin on enzyme activity. This hypothesis is consistent with our previous findings [6]: glucocorticoid supply partially overcomes the paradoxical effect of actinomycin D on enzyme activity. Since the stim ulatory effect of the antibiotic on OTC activ ity is associated with a decrease in insulincmia, glucocorticostcroids and the high level in fetal insulinentia [3,18] might act as inhib itory factors on enzyme development, sug gesting a permissive effect of glucocorticosteroids on insulin action in vivo.…”
Section: Discussionsupporting
confidence: 94%
“…Our ear lier studies showed that the activities of CPS-I and OTC are low in the fetus and increase rapidly after birth [4], We also reported that both activities are affected by the deprivation of glucocorticoids during the late fetal period [5]. Moreover, a hydrocortisone acetate sup ply to intact fetuses increased the level of CPS-I activity 3 days later, while OTC activ ity exhibited a paradoxical increase after an actinomycin D supply [6]. In further experi ments, we found that the inhibitory effect of glucose on postnatal increase in OTC activity might be associated with the resulting in crease in insulinemia [7].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Even during the fetal period, however, glucocorticoids may have both stimulatory and inhibitory influences in the liver. For example, glucocorticoid suppresses amylo-l,6-glucosidase activity in fetal rat liver [57] and inhibits DNA synthesis in the liver of weanling rats [24], but in low doses enhances the activity of carbamoylphosphate synthetase-I [22] and conversion of T4 to T3 [61] in the fetal liver. The weanling rat has marked recuperative powers after glucocorticoid treatment as shown by increases in liver DNA polymerase activity [25] and ornithine decarboxylase [20], and complete recovery of DNA content by 8 days of recovery [25].…”
Section: Discussionmentioning
confidence: 99%
“…Freshly excised livers were imme diately weighed and homogenized in 0.1% A'-cetyl-N,N,N-trimethylammonium bromid (CTB) (4) (Merck, Darmstadt) in the ratio 1 g liver to 7 ml o f C T B for the assay of carbamylphosphate synthetase-I and orni thine transcarbamylase. After two successive centri fugations for 15 min at 4,000 g at 5 °C , the enzymatic activities were assayed on the supernatant solution according to the method o f Brown and Cohen (4) with some modifications as previously described (11). Enzyme Unit.…”
Section: Delivery By Cesarian Section Onmentioning
confidence: 99%